A New Stepless Control Concept for Multi-Lane Bottle Conveyors - Sorgatz, André; Gabler, Fabian; Voigt, Tobias (BrewingScience, 2010)
Multi-lane bottle conveyors are in use at almost all bottling plants. They are not only needed for the transportation of bottles but also for decoupling the failure sensitive machines of the plant by storing and providing bottles. This increases the overall efficiency of a plant by bridging short downtimes. These buffer conveying systems have to be controlled with regard to their filling level. State of the art is the stepwise detection of the filling level by mechanical switches, which are actuated by accumulating bottles. This leads to a stepwise control. In this paper a new control concept is presented which allows controlling multi-lane conveyors stepless by monitoring the infeed and the output of the conveyor. This enables a more precise control of the conveyor sections velocities and outputs of the up- and downstream machines. No mechanical jam switches are necessary. The developed control algorithm was successfully implemented and tested at an industrial scale pilot plant. Test runs showed an equal flow of bottles due to the continuous adaption of the machine outputs and conveyor sections velocities and the minimization of the conveyors dead time.